ESG (Environmental, Social, Governance) Integration in Global Islamic Finance - Judijanto, Loso; Fathoni, Ahmad Iqbal; Fauziah, Diah; Lasmiatun, KMT; Ashari, Muhammad Idris (West Science Islamic Studies, 2025)
ESG integration is emerging as a game-changing influence on the world's financial systems with wide-ranging consequences for the Islamic finance industry. This research, therefore, has been designed to reach an objective that presents compatibility, challenges, and opportunities concerning ESG adoption in Islamic finance through a systematic review of 22 peer-reviewed manuscripts indexed in the Scopus database. The findings identify a good coincidence between ESG best practices and Sharia principles, as both witness vital echoes on ethical behavior, social development, and sustainability. Good harmony has been noted, though regulatory disparity, weak frameworks, and lack of awareness stand in the way. Green sukuk and international collaboration are promising pathways for the arising ESG issues. This would provide actionable insights for policymakers and financial institutions so that sustainability and ethical value creation can be encouraged at large, while positioning Islamic finance as a world leader in sustainable finance.